2020
DOI: 10.1177/2633494120906010
|View full text |Cite
|
Sign up to set email alerts
|

Surgical adhesions among women undergoing laparoscopic gynecological surgery with or without adhesiolysis – prevalence, severity, and implications: retrospective cohort study at a University Hospital

Abstract: Objective: To find out the prevalence of adhesions, severity, and their relation to the current clinical scenario and to the type of previous surgery. Methods and Materials: A retrospective study of patients who already had different previous abdominopelvic surgery and subsequently underwent gynecological laparoscopic surgery for various indications. The patients’ clinical and operative notes were reviewed and analyzed. Results: There were 654 procedures performed. The most common indication for the laparoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…[ 5 19 ] Our finding also contrasts an observation from Ghana, in a study involving repeat cesarean section, which reported a prevalence of 38% adhesion formation rate among women who had undergone prior cesarean section. [ 7 ] A similar study from Jordan reports a prevalence of 45.3%,[ 9 ] which is lower than observed in our center. A much lower rate of 21.1% was observed by Dubuisson et al .…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…[ 5 19 ] Our finding also contrasts an observation from Ghana, in a study involving repeat cesarean section, which reported a prevalence of 38% adhesion formation rate among women who had undergone prior cesarean section. [ 7 ] A similar study from Jordan reports a prevalence of 45.3%,[ 9 ] which is lower than observed in our center. A much lower rate of 21.1% was observed by Dubuisson et al .…”
Section: Discussionmentioning
confidence: 40%
“…Most of these women have had prior abortions which is a recognized risk factor for secondary infertility due to tubal, endometrial or peritoneal disease. [ 5 9 19 20 ] Unsafe abortion is a recognized risk factor for pelvic infection, including adhesion formation and infertility. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intra abdominal adhesions were present in 36.1% of the patients which was lower when compared to our study. 13 A study reported that 45.1% of patients with a history of CS showed evidence of pelvic adhesions during the ultrasonographic examination. 14 Our study had shown that the mean operating time was higher in severe adhesions than mild adhesions which was comparable to another similar study.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, IPAA procedures were performed in an open fashion; however, with advances in medical technology, a minimally invasive approach using laparoscopy is now preferred, which has made recovery time quicker and the likelihood of adhesions lower [ 17 , 18 ]. Adhesions are considered unfavourable as these can lead to a higher chance of postoperative complications; however, a recent paper by Dionigi et al [ 19 ] suggests that this decrease in adhesions through using laparoscopy, in fact, predisposes the pouch and its proximal small bowel to volvulus.…”
Section: Discussionmentioning
confidence: 99%